2018
DOI: 10.19126/suje.398201
|View full text |Cite
|
Sign up to set email alerts
|

Beden Eğitimi ve Spor Öğretiminde Alternatif Ölçme ve Değerlendirme Üzerine Bir İnceleme

Abstract: Öz. Bu araştırmanın amacı, beden eğitimi öğretmenlerinin alternatif ölçme değerlendirme araç, yöntem ve yaklaşımlarını önemseme ve kullanma düzeylerinin paydaş görüşleri eşliğinde incelenmesidir. Araştırma, karma yöntemde gerçekleştirilmiştir. Araştırmanın örneklemini 2016 -2017 eğitim öğretim yılında Manisa ve İzmir illerinde görev yapan beden eğitimi öğretmenleri (440 öğretmen; özel n=215, devlet n=225) oluşturmaktadır. Nicel verilerin elde edilmesinde, Balcı ve Tekkaya'nın (2000) ölçeğinden yararlanılarak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…In this study and many other studies presented above, the aim is to reduce bias by using different evaluation structures and different evaluators to prevent this. Physical education teachers attached importance to self and peer evaluation techniques but they were found to have low frequency in using them (Asma et al, 2018). This may be caused by the fact that they do not have the chance to try what they have learnt as the content during their assessment and evaluation lessons in terms of field-specific practical transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study and many other studies presented above, the aim is to reduce bias by using different evaluation structures and different evaluators to prevent this. Physical education teachers attached importance to self and peer evaluation techniques but they were found to have low frequency in using them (Asma et al, 2018). This may be caused by the fact that they do not have the chance to try what they have learnt as the content during their assessment and evaluation lessons in terms of field-specific practical transfer.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with physical education teachers, they showed a low rate of frequency in self-assessment and peer review techniques, but a very high frequency in terms of caring level (Asma, Çamlıyer, Soytürk, Balcı, & Çamlıyer, 2018). Such a result shows that physical education teachers consider these two alternative evaluations techniques as important, but that they do not use these in a parallel way.…”
Section: Introductionmentioning
confidence: 98%
“…Beden eğitimi dersi akademik başarıya tam olarak etki etmediği gibi ölçme değerlendirmenin doğru şekilde yapılamaması öğretmenlerin problem yaşamamak için yüksek not verme eğiliminde olmalarını sağlamaktadır. Bu nedenle aileler, öğrenciler ve veliler yüksek not beklentisi içindedir (Asma, Çamlıyer, Soytürk, Balcı, Çamlıyer, 2018;Özkoparan ve İnan, 2018;Uğraş ve Sağın, 2019;Zhu, 2015).…”
Section: öLçme Ve Değerlendirme Ile Ilgili Sorunlarunclassified